Molecular Architectures Derived from Metal Ions and the Flexible 3,3′-Bipyridine Ligand: Unexpected Dimer with Hg(II) - Anupam Khutia; Pablo J. Sanz Miguel; Bernhard Lippert (Bioinorganic Chemistry and Applications)
The flexible ditopic ligand 3,3-bipyridine (3,3-bpy) has been reacted with a series of transition metal species (Ag+, Hg2+, cis-a2M2+ (a=NH3 or a2=en; M=Pt,Pd), trans-a2Pt2+ (a=NH3)) in an attempt to produce discrete cyclic constructs. While Ag+ gave a polymeric structure {[Ag(3,3-bpy)](ClO4) ⋅ H2O}𝑛 (1), with all other metal entities cyclic structures were formed. Interestingly, Hg(CH3COO)2 produced a dinuclear complex [Hg(3,3-bpy)(CH3COO)2]2 ⋅ 3H2O (2), in which the two 3,3-bpy ligands adopt a cis-orientation of the coordinating pyridyl entities. With cis-(NH3)2Pt2+, a cyclic complex 4 was isolated in crystalline form which, according to HRMS, is a trimer. With trans-(NH3)2Pt2+, different species are formed according to 1H NMR spectroscopy, the nature of which was not established.